(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s ((3Ydj eMeO GdMhjRjs)
(3ChdgG (B:s
(3cjaeG cGfJ hYdi cd MGd adG ETcGd aj UMI GdUdGI HSH GMJeGd GdQNUI aj GdbQGAI (B...s
(3BNQgG (B:s
(3hef jYde Cf eQGOg GdQLMGf aj GdLedI dGMJeGd Tehd GdNHQ dPdc hgh dG QjH ajg(B... (3bO Je gPG GdLRAs
(3ebGHdI (B1(3Ph GdMLI, SfI(B1353(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B373s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B214s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B378s
Keywords: (3abg GdePGgH GdCNQis